Carbon and nitrogen mineralization kinetics in soil previously amended with sewage sludge - Paul, Eldor A., author; Boyle, Michael, author; Soil Science Society of America, publisher (Colorado State University. Libraries, 1989)
Microbial mineralization rates of organic carbon (C) and nitrogen (N) were determined on the same sludge-amended and nonamended soil samples. The purpose of this integrated approach was to high-light the long-term dynamics of N release with C stabilization in sludge-affected soil. Three application rates of digested municipal sludge, check, 45 Mg ha−1 and 180 Mg ha−1, were incorporated into field plots annually for 8 years, with no addition during the subsequent 3 years. Barley was grown on the site each spring of the 11 years. In an 87-week laboratory incubation experiment conducted on soil samples collected 3 years after the last sludge addition, N and C mineralization rates (kn, kc) increased with sludge application rate. Soil nitrogen mineralization potentials (No) increased with sludge application, unlike carbon mineralization potentials (Co) which did not correlate with sludge application. The C/N ratio of the mineralized organic matter decreased with sludge application rate. Three years after field incorporation of sludge, decomposition of the organic fraction can be described as a set of two first-order rate reactions. One fraction is characterized by a large stable element (high No, Co and low kn, kc); the second fraction consists of a smaller labile portion which is characterized by low No, Co and high kn, kc values. The microbial biomass decreased to less than half of its original amount after 20 weeks of incubation in all soil treatments.
Keywords: SOM; organic waste; N mineralization